Evidence for an environmental effect in the aetiology of insulin dependent diabetes in a transmigratory population. Issue 6833 (18th April 1992) - Bodansky, H. J.; Staines, A.; Stephenson, C.; Haigh, D.; Cartwright, R.
Abstract : OBJECTIVE–To examine whether children of families moving from an area of low incidence of childhood diabetes to one which is higher show a corresponding rise in disease incidence. DESIGN–Disease incidence study over 12 years. SETTING–Bradford District Metropolitan Council area. SUBJECTS–All subjects aged 0-16 years resident within the study area. MAIN OUTCOME MEASURES–The incidences of childhood diabetes in Asian and non-Asian families. RESULTS–The incidence of diabetes in Asian children increased from 3.1/100, 000 per year in 1978-81 to 11.7/100, 000 per year in 1988-90 (chi 2 for trend = 4.95, df = 1, p = 0.026) whereas that for other children remained constant at 10.5/100, 000 per year. Over the entire study period rates were lower in Asian females (4.9/100, 000 per year) than in Asian males (8.8/100, 000 per year) whereas the reverse was true for other children (males 9.2/100, 000 per year; females 12.0/100, 000 per year) (test for common odds ratio: chi 2 = 3.81, df = 1, p = 0.052). CONCLUSIONS–Offspring of this transmigratory population had a rising incidence of childhood diabetes which was approaching that of the indigenous population. The data provide strong evidence for an environmental effect in the aetiology of insulin dependent diabetes.